The Impact of Technological Innovation on Environmental Governance in the Logistics Industry - Zheng, Yanan; Sheng, Panlong (Asia Pacific Economic and Management Review, 2025)
This article uses relevant data from 30 provinces, autonomous regions, and municipalities in China from 2014 to 2023 as research samples to empirically test the impact of technological innovation on logistics industry environmental governance. The results show that: (1) the benchmark regression results show that technological innovation has a positive impact on logistics industry environmental governance. (2) The results of the mediation effect test show that new quality productivity and market mechanisms play a partial mediating role in the relationship between the two. (3) Heterogeneity tests indicate that technological innovation has a more significant impact on the environmental governance of the logistics industry in the eastern region than in the central and western regions.